Centro articulador interactivo de tecnología, innovación y cultura Bazurto (2019)
The Bazurto market is the central of supplies of the city of Cartagena. It is an area with great urban dynamism, full of shops and a lot of culture. However, it has been perceived by the majority of Cartagena as a problematic, insecure site and as a source of contamination. Its location is privileged, because it is in the center of the city, and in its vicinity is the marsh of the Quintas; In addition, we have an architectural milestone known as “the market building” whose state of deterioration is increasing. The present investigation uses a methodology that goes from the general to the particular to find a problem as a space between a lived situation and a desired situation, identifiable identification through the systemic scales: macro, meso and micro, to which proposals will be made. so-called products, whether urban or architectural. The project’s approach arises from the variables studied at the site, based on the city’s POT as the main axis of the legal framework. This thesis aims to expose an advanced basic scheme, defined by the authors as CAITIC: interactive articulator center of technology, innovation and culture, together with a comprehensive proposal of urban renewal for the rehabilitation of the sector, which you read They would give a new and better character to the area. It includes a cultural center, a technological park, a multimodal station articulated with public transport and public space around the marshes of Las Quintas